g-C3Nx@CN composite preparation and its photocatalytic degradation property under visible light - ZHU Yiren; HE Chunpeng; NIE Xuetong; GAO Zhong; LI Ying (Cailiao gongcheng)
A photocatalyst g-C3Nx@CN with defective carbon nitride （g-C3Nx） encapsulated by CN shells is prepared by in-situ growth and high-temperature dezincification. The structural， morphological， and compositional characterization of g-C3Nx@CN has been analyzed and characterized by various analytical means. First， g-C3Nx with nitrogen defects is prepared by high-temperature polycondensation of melamine and high-temperature denitration of Mg powder， followed by in-situ growth of ZIF-8 by loading ZnO nanoparticles. Finally， g-C3Nx@ZIF-8 is dezincified at high temperature， and the CN shell-encapsulated visible light catalyst material g-C3Nx@CN with double defects （N， Zn） with ZIF-8 is prepared. The study demonstrates that the g-C3Nx@CN catalyst exhibits strong visible photocatalytic activity and effectively degrades methylene blue and 2，4-dichlorophenol within 240 min， with the best performance of the g-C3Nx@CN-5∶4 composite. The single linear oxygen （1O2） plays a dominant role in the reaction system. In the cycle test， the g-C3Nx@CN shows excellent recycling and light stability. This study extends the study of defective carbon nitride materials in visible light absorption and provides a viable method for the derivation of metal catalysts to inorganic non-metal catalysts.